Haplotyping of Echinococcus granulosus Isolates From Human, Sheep and Cattles Hydatid Cysts in Some Central Euphrates Provinces, Iraq - Nabaa Zahid Sabri Shani Al-Hasnawi; Ahmed Khudhair Al-Hamairy; Huda Jasim M. Altameme (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study included nine samples collected from the infected (liver and lung) divided into three equal samples (sheep, cattle and humans) collected from some Central Euphrates Provinces for the period from the beginning August 2019 till February 2020. PCR technique was performed for in detection and genotyping of Echiococcus granulosus hydatid cyst based on mitochondrial Cox1 gene and Nad1 genes in isolates. This technique was carried out according to method described by Nikmanesh et al. (2014). The present study aimed to showed haplotype genetic and the frequency percentage of it in the Central Euphrates region. the result showed the H15 haplotype was a higher frequency followed it ( H10, H11) and then (H5). The frequency percentage of the haplotype genetic in the current study of the taken samples (8) that the prevalence and frequency of haplotype genetic H15 was 37.5%, followed by the genotype ( H10,H11) at 25% for both them , and the lowest was the genotype (H5) at 12.5% The human samples registered 100% for (H15) , the sheep registered 50 % for H5, H10.While cattle samples registered 33.3 % for H10 and 66.6 for H11 . Isolation H15 is the essential in the infection to humans as a result of dogs were fed hydatid cysts of cattle origin, and there is no relationship between sheep and humans, while there is a relationship between sheep and cattle in the Haplotype (H10).